2018
DOI: 10.18273/revuin.v17n1-2018004
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of the mechanical and vibratory properties of a composite reinforced with fique fibers versus a composite with E-glass fibers

Abstract: Este artículo puede compartirse bajo la licencia CC BY-ND 4.0 y se referencia usando el siguiente formato: S. Gómez, B. Ramón, R. Guzmán, "Comparative study of the mechanical and vibratory properties of a composite reinforced with fique fibers versus a composite w ith E-glass fibers," Rev. UIS Ing., vol. 17, no. 1, pp. 43-50, 2018. Doi: https://doi.org/10.18273/revuin.v17n1-2018004 Vol. 17, no. 1, pp. 43-50, enero-junio 2018 Revista UIS Ingenierías ABSTRACTIn the following research, the mechanical and dyna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 19 publications
0
9
0
4
Order By: Relevance
“…Fique natural fibres (furcraea andina), supplied by Coohilados del Fonce Ltd., were used. The fique fibre has a density of 0,72 g/cm 3 , for a linear density of 31,32 tex, with an average cross-section of 0,176 mm 2 and a diameter of 0,473 mm [20]. Applying descriptive statistics, it was found that the yarn used is formed of approximately 29 fibres with an estimated diameter of 0.016 mm and an apparent thread diameter of 1.444 mm.…”
Section: Methodsmentioning
confidence: 99%
“…Fique natural fibres (furcraea andina), supplied by Coohilados del Fonce Ltd., were used. The fique fibre has a density of 0,72 g/cm 3 , for a linear density of 31,32 tex, with an average cross-section of 0,176 mm 2 and a diameter of 0,473 mm [20]. Applying descriptive statistics, it was found that the yarn used is formed of approximately 29 fibres with an estimated diameter of 0.016 mm and an apparent thread diameter of 1.444 mm.…”
Section: Methodsmentioning
confidence: 99%
“…Muchos materiales cerámicos y poliméricos tienen limitaciones mecánicas que pueden ser reducidas utilizando elementos de refuerzo en diferentes escalas como el acero, fibras metálicas, fibras vegetales [13], microfibras de polipropileno [14]. De esta forma, los geopolímeros se tornan una matriz y el elemento de adicionado actúa como refuerzo frente a las debilidades de la matriz principal.…”
Section: Geopolímerosunclassified
“…Las fibras cortas de fique utilizadas presentaron una longitud promedio de 1,76 ± 0,53 mm y un diámetro de 0,0253 ± 0,0033 mm, como se evidenció en la realización de la medición por medio de microscopia electrónica de barrido SEM en un estudio anterior realizado por los autores [25].…”
Section: Materialesunclassified